SISTEM PAKAR UNTUK MENDETEKSI KESALAHAN ELEKTRODA PADA PROSES WELDING FRAME THERMOSTAT PADA SOULPLATE MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB (STUDI KASUS PT PHILIPS) - riski, sestri novia (STKIP PGRI Sumatera Barat, 2017)
The use of SMAW (Shielded Metal Arc Welding) in the industrial world is enough widely used. With this machine the human greatly helped by the need to make a metal object. So that by the frequent use of these tools, the more susceptible it is also a tool damage. Technicians machines supplied by the company are not proportional to the number of machines. Therefore, to help resolve this issue needs an expert system that can act as an assistant to the engineer. Data relating to the damage processed using forward chaining expert system. Expert systems are made using the programming language PHP and MySQL database so as to produce an expert system to detect damage SMAW web based. So it can help technicians solve problems SMAW and can also be used for the source of knowledge about the condition and its causes and solutions to overcome them.